IMPLEMENTATION OF NEW EDUCATION POLICY: PERCEPTION AND PROFESSIONAL ADAPTATION OF SECONDARY SCHOOL TEACHERS IN KHULNA - Shaikh, Hasan; Hossen, Md. Iqbal (IJIET (International Journal of Indonesian Education and Teaching), 2025)
In an era where educational reforms serve as both a beacon of hope and a source of contention, the New Education Policy (NEP) of Bangladesh emerges as a critical site for exploring the dynamic interplay between policy ideals and classroom realities. Grounded in the Theory of Planned Behavior, it seeks to examine teachers interpretations and responses to policy reforms, their challenges and opportunities, and the impact of the NEP on education quality. The study employs a mixed-methods approach, combining a survey of 48 teachers from seven distinct schools, with nine providing in-depth interviews. The findings reveal significant discrepancies in teachers understanding of the policys objectives, with a notable portion expressing dissatisfaction with its clarity and alignment with student needs. While some educators acknowledge a shift towards student-centered learning, others highlight the obstacles posed by insufficient resources, professional development, and curriculum adjustments. However, to address the limitations of this study, future studies can expand the scope to include different regions and explore the long-term effects of NEP on student outcomes. Furthermore, educators and policymakers must collaborate to ensure that ongoing professional development and resource allocation are prioritized to facilitate successful educational reform.